Penerapan Metode Mastery Learning pada Animated Pedagogical Agent (APA) untuk Pembelajaran Aksara Jawa - Aryasatya Okta Pradhana; Ati Suci Dian Martha; Anisa Herdiani (STMIK Budi Darma, 2024)
Javanese script learning is learned by students in elementary schools in Tuban, East Java. However, students still do not understand this Javanese script learning material. This is related to students' low interest in learning. This research aims to evaluate the impact of the application of mastery learning method through Animated Pedagogical Agent on students' interest level in learning Javanese characters. In addition, to develop a learning application